2023
DOI: 10.3390/machines11121081
|View full text |Cite
|
Sign up to set email alerts
|

Bioinspired Design of Material Architecture for Additive Manufacturing

Dairon Pleasant,
Connor Gavin,
Garrett Redden
et al.

Abstract: This research explores the enhancement of mechanical properties in material architectures, such as strength-to-weight ratio and resilience, through the inspiration of natural systems. Historically, designs for additive manufacturing have relied on simple, repetitive structures like honeycombs, often leading to unnecessary material expenditure. This study aims to examine the compressive mechanical attributes of designs inspired by natural systems, including bird nests, cocoons, and the layered structure of skul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Grass stalks and horsetails were found to have considerable bending and distortion stiffness based on interconnected ring structures that allow for a beneficial axial second moment of area [10]. In [11], biomimetic infill structures based on a bird nest, a cocoon, trees, turtle shells, and bone were investigated. This study focused on additively manufactured samples and found great potential for the designs for the three objectives of maximal supported load in compression, resilience, and strengthto-weight ratio.…”
Section: Biological Role Modelsmentioning
confidence: 99%
“…Grass stalks and horsetails were found to have considerable bending and distortion stiffness based on interconnected ring structures that allow for a beneficial axial second moment of area [10]. In [11], biomimetic infill structures based on a bird nest, a cocoon, trees, turtle shells, and bone were investigated. This study focused on additively manufactured samples and found great potential for the designs for the three objectives of maximal supported load in compression, resilience, and strengthto-weight ratio.…”
Section: Biological Role Modelsmentioning
confidence: 99%